2007
DOI: 10.1007/s11205-007-9113-7
|View full text |Cite
|
Sign up to set email alerts
|

A note on the score reliability for the Satisfaction With Life Scale: an RG study

Abstract: Life satisfaction, Reliability generalization, Meta-analysis, Satisfaction With Life Scale, SWLS, Psychometric,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
78
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 71 publications
15
78
1
5
Order By: Relevance
“…A later study found a moderate mean Cronbach's alpha coefficient (α = 0.78) for the SWLS and attributed the moderate score to the small number of items in the scale [44].…”
Section: Subjective Wellbeing Measurementioning
confidence: 97%
“…A later study found a moderate mean Cronbach's alpha coefficient (α = 0.78) for the SWLS and attributed the moderate score to the small number of items in the scale [44].…”
Section: Subjective Wellbeing Measurementioning
confidence: 97%
“…Female sexual function index is a scale used to measure sexual function in women. This scale has been designed by Rosen [22]. The reliability of the scale and subscale was calculated through Cronbach's alpha coefficient that was estimated more than 0.70 for the total population indicating good reliability of this instrument.…”
Section: Data Used In This Study Were As Followmentioning
confidence: 99%
“…This opposing relationship has been reiterated in the gerontological literature as the paradox of well-being (Fernández-Ballesteros, 2007;von Humboldt, 2016;Wrosch, Scheier, Carver, & Schulz, 2003). Moreover, some inconsistent results were found in relation to the validity and reliability of the Satisfaction with Life Scale (SwLS) in older samples (Vassar, 2008;Vassar, Ridge, & Hill, 2008); hence there is a need for more research focused on SwL with older adults.…”
mentioning
confidence: 99%